2014
DOI: 10.4172/2155-9546.1000284
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, Antioxidants and Antimicrobial Activities of Lipids Extracted from Some Marine Algae

Abstract: to whom the authors are very indebted. Extraction and determination of total lipids Total lipids of marine algae (100 g) were extracted according to the method described by Roughan and Bratt [9].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Seaweed cultivation is economically viable due to the presence of high-value compounds in algae cells, which are extracted and used for the manufacture of cosmetics, pharmaceuticals, and chemical compounds. El-baz et al [17] showed that among species of red and green algae, U. lactuca had a higher lipid concentration and inhibitory actions on viral and bacterial activities. In industry, macroalgae have wide applicability, with them being a good nutritional alternative and having a good acceptability, as shown by Turan and Tekogul [18].…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed cultivation is economically viable due to the presence of high-value compounds in algae cells, which are extracted and used for the manufacture of cosmetics, pharmaceuticals, and chemical compounds. El-baz et al [17] showed that among species of red and green algae, U. lactuca had a higher lipid concentration and inhibitory actions on viral and bacterial activities. In industry, macroalgae have wide applicability, with them being a good nutritional alternative and having a good acceptability, as shown by Turan and Tekogul [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ulvophyceae are the family of green seaweeds that occur in marine and brackish water ecosystems. Ulva fasciata come under this family and are abundant in the marine ecosystem [12] . The plenitude of this species created scope in the field of food and biomedical industries.…”
Section: Introductionmentioning
confidence: 99%